2021
DOI: 10.1186/s13104-021-05556-1
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of schema therapy for young adults with high-functioning autism spectrum disorder: a single-arm, uncontrolled trial

Abstract: Objective Psychological problems associated with isolation and mistrust are common among young adults with autism spectrum disorder (ASD). Schema therapy (ST) has recently been shown to be effective against chronic personality problems of various mental disorders, including personality disorders. This pilot clinical trial aimed to explore the feasibility and acceptability of ST in young adults with high-functioning ASD. Results Following the interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Sixteen articles described studies of mental health interventions that had been adapted to make them more appropriate for autistic people. These included adaptations of Cognitive Behavioural Therapy (CBT) for anxiety (49,50,58), CBT for OCD (30,51), mindfulness-based therapy for autism spectrum disorders (MBT-AS) (31,53), Eye Movement Desensitisation and Reprocessing (EMDR) (36,43), guided self-help CBT for depression (33,38), acceptance and commitment therapy (ACT) (56), Schema therapy (55), mindfulness-based stress reduction (MBSR) (37), CBT for anxiety and depression (37), CBT aimed to reduce general psychological distress (42,45). No trials directly compared adapted and non-adapted mental health interventions; hence no conclusions could be drawn as to whether specific adaptations resulted in better outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen articles described studies of mental health interventions that had been adapted to make them more appropriate for autistic people. These included adaptations of Cognitive Behavioural Therapy (CBT) for anxiety (49,50,58), CBT for OCD (30,51), mindfulness-based therapy for autism spectrum disorders (MBT-AS) (31,53), Eye Movement Desensitisation and Reprocessing (EMDR) (36,43), guided self-help CBT for depression (33,38), acceptance and commitment therapy (ACT) (56), Schema therapy (55), mindfulness-based stress reduction (MBSR) (37), CBT for anxiety and depression (37), CBT aimed to reduce general psychological distress (42,45). No trials directly compared adapted and non-adapted mental health interventions; hence no conclusions could be drawn as to whether specific adaptations resulted in better outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, high levels of attendance, retention, homework compliance and treatment credibility were reported regarding group ACT (56) One study reported a high attendance rate to adapted CBT for anxiety (45). A study of CBT for anxiety (58) and a study of schema therapy (55) reported low drop-out rates. Most participants found the adaptations (i.e., use of visualisation) of CBT for anxiety to be helpful (50).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation might be that these modes are persistent due to the vulnerability to maladaptive schema development in autistic people (Gaus, 2019), though the changes in core beliefs contradict this explanation. In a study, examining ST in young autistic adults, a delayed change in schema modes compared to early maladaptive schemas was found, suggesting schema modes to be more stable than early maladaptive schemas (Oshima et al, 2021). Another explanation might be that the ST primarily strengthened functional modes, while not successfully addressing the dysfunctional modes in autistic people.…”
Section: Discussionmentioning
confidence: 99%
“…Early maladaptive schemas appear to account for mental health conditions in adults with autism spectrum conditions (Oshima et al, 2014). A single‐arm preliminary study with an open trial design ( N = 10, aged 20 to 39 years, 5 males, 5 females) indicated that individual ST is applicable as a treatment for young autistic adults with mental health conditions (no PD), showing a significant reduction in early maladaptive schemas and improvement in quality of life and social adjustment (Oshima et al, 2018; Oshima et al, 2021).…”
Section: Introductionmentioning
confidence: 99%